2006
DOI: 10.1021/cm0612090
|View full text |Cite
|
Sign up to set email alerts
|

Strong Reduction of Thermal Conductivity in Nanostructured PbTe Prepared by Matrix Encapsulation

Abstract: Developing advanced thermoelectric (TE) materials can impact conversion technologies of waste heat to electrical power. It is well expected that by fabricating TE materials in a nanostructured form their properties can be significantly enhanced. 1 Efficient TE materials must exhibit a large TE figure of merit, ZT, defined as ZT ) σS 2 /κ, where S is the TE power (absolute Seebeck coefficient), σ is the electrical conductivity, and κ is the thermal conductivity. The Seebeck coefficient is generally inversely re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
128
1
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 179 publications
(147 citation statements)
references
References 21 publications
13
128
1
4
Order By: Relevance
“…There are, moreover, studies showing that introducing barriers like grain boundaries in polycrystalline samples may scatter long-wavelength acoustic phonons, thus reducing κ even further [19,24,[26][27][28][29][30][31], in particular for nanostructured bulk samples [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…There are, moreover, studies showing that introducing barriers like grain boundaries in polycrystalline samples may scatter long-wavelength acoustic phonons, thus reducing κ even further [19,24,[26][27][28][29][30][31], in particular for nanostructured bulk samples [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] The prototypical example is PbTe, with a approaching 1.0. 13 It has recently been shown that alloying PbTe with other semiconductor systems can increase the figure of merit through the formation of nanoscale precipitates, which reduce the lattice thermal conductivity, , of the system without significantly reducing the electronic conductivity, .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, increasing such conversion efficiency requires both high ZT and a large temperature gradient across the materials. One effective way to achieve high ZT is to reduce lattice thermal conductivity through embedding micro/nanostructures, which provide multiple scattering mechanisms for phonons 1,2,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] . Other strategies address the challenge of maximizing a power factor from existing semiconducting materials by band alignment 5,6,19,20 , modifying their electronic structures close to the Fermi level 21,22 , and increasing band degeneracy by convergence of bands 23 .…”
mentioning
confidence: 99%